Molecular determinant for the tarantula toxin Jingzhaotoxin-I slowing the fast inactivation of voltage-gated sodium channels. (1st March 2016) - Tao, Huai; Chen, Xia; Lu, Min; Wu, Yuanyuan; Deng, Meichun; Zeng, Xiongzhi; Liu, Zhonghua; Liang, Songping
Abstract: Peptide toxins often have divergent pharmacological functions and are powerful tools for a deep review on the current understanding of the structure-function relationships of voltage-gated sodium channels (VGSCs). However, knowing about the interaction of site 3 toxins from tarantula venoms with VGSCs is not sufficient. In the present study, using whole-cell patch clamp technique, we determined the effects of Jingzhaotoxin-I (JZTX-I) on five VGSC subtypes expressed in HEK293 cells. The results showed that JZTX-I could inhibit the inactivation of rNav1.2, rNav1.3, rNav1.4, hNav1.5 and hNav1.7 channels with the IC50 of 870 ± 8 nM, 845 ± 4 nM, 339 ± 5 nM, 335 ± 9 nM, and 348 ± 6 nM, respectively. The affinity of the toxin interaction with subtypes (rNav1.4, hNav1.5, and hNav1.7) was only 2-fold higher than that for subtypes (rNav1.2 and rNav1.3). The toxin delayed the inactivation of VGSCs without affecting the activation and steady-state inactivation kinetics in the physiological range of voltages. Site-directed mutagenesis indicated that the toxin interacted with site 3 located at the extracellular S3–S4 linker of domain IV, and the acidic residue Asp at the position1609 in hNav1.5 was crucial for JZTX-I activity. Our results provide new insights in single key residue that allows toxins to recognize distinct ion channels with similar potency and enhance our understanding of the structure-function relationships of toxin-channel interactions. Highlights: JZTX-I inhibited the inactivation of rNav1.2, rNav1.3, rNav1.4, hNav1.5 and hNav1.7 channels with low selectivity. JZTX-I delayed the inactivation of VGSCs without affecting the activation and steady-state inactivation kinetics. The acidic residue Asp at the position1609 in the extracellular S3–S4 linker of domain IV was crucial for JZTX-I activity.